Empirical analysis of crude oil consumption and price on Ghana’s economic growth - Appiah, Gideon Kweku; Oduro, Ebenezer; Benn, Shadrack (Open Science Journal, 2020)
Abstract The objective of this paper was to investigate the impact of crude oil consumption and oil price on the growth of the Ghanaian economy. It proceeded with annual time series data (1980-2016) sourced from World Development Indicator (WDI) and Energy Information Administration (EIA). All variables used in the study were integrated of order one as suggested by the Augmented Dickey-Fuller (ADF) test. Further, the Johansen Cointegration test suggested the existence of cointegration among the variables. The study used the OLS estimation procedure. The study found a positive and statistically significant relationship between oil price and economic growth in the long run. On the other hand, an inverse relationship was found between crude oil consumption and economic growth in the long run. Based on the findings the study recommends that the government diversify the economy to reduce the shock the economy might experience in times of oil price shocks. Further, risk management instruments like physical reserves and hedging against oil prices should also be employed. Also, the study recommends policies that encourage efficient consumption of crude oil, especially in the productive sectors like industry in order to trigger growth. This notwithstanding, the study recommends effective measures to mitigate the externalities associated with increased production and consumption of crude oil, such as the carbon tax.